Preparation and Electrochemical Performance of a Graphene Cathode Catalyst Decorated With Pt by Prolysis - Wang, Xi; Ren, Ying; Suo, Ni; Zhang, Guifeng (Frontiers in Energy Research, 2022)
Graphene cathode catalysts for fuel cells with controllable platinum content were decorated by pyrolyzing chloroplatinic acid under various process parameters to obtain a high catalytic activity and durability. The structural characteristics of catalysts were investigated by SEM, TEM, XRD, and Raman spectroscopy. The oxygen reduction reaction catalytic activity was measured by cyclic voltammetry (CV) and linear sweep voltammetry (LSV), and the durability of the catalyst was characterized by use of the i-t curve. Compared with the commercial Pt/C (20 wt.% Pt) catalyst, the initial potential and the current density retention rate of the catalyst decorated with 8% platinum are 55 mV and 23.7% higher, respectively. The catalysts prepared in the present research exhibits superior catalytic activity and stability.